Rhynchosia waterbergensis (Cajaninae, Phaseoleae, Fabaceae), a new unifoliate species from Waterberg, South Africa - Ajao, Abdulwakeel Ayokun-Nun; Boatwright, James Stephen; Moteetee, Annah Ntsamaeeng (Phytotaxa, 2018)
A new unifoliolate species of Rhynchosia from Modimolle (formerly Nylsroom), in the Waterberg area, South Africa, was discovered. Until now, R. monophylla was the only unifoliolate species of the genus in southern African, however, the two differ markedly in growth habit; the former species is a trailing herb, while the new species is an erect subshrub. This species is closely similar to R. spectabilis in having a canescent-tomentose indumentum that covers the whole plant, broadly ovate or ovate-orbicular leaves, and pubescent standard petals, but differs mainly in the unifoliate leaves, length of the inflorescence, and number of flowers. Here we describe the new species Rhynchosia waterbergensis in the type section Rhynchosia.